2013
DOI: 10.1177/1934578x1300800102
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Conditions and Herbivory Effects on Morphological Plasticity of Argania spinosa

Abstract: The main objective of this paper was to look into the morphological differentiation patterns and phenotypic plasticity in four populations of Argania spinosa with environmentally contrasted conditions. Mean response, magnitude and pattern of morphological intra-and inter-population plasticity indexes were measured and analyzed in order to identify which characters contribute the most to the acclimation of this species. Populations growing in the ecological optimum of the species presented the lowest plasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Grazing generally has a negative effect on plants [13][14][15][16][17].In a previous work conducted in Admine forest, a heavily humanized area traditionally managed for livestock raising and agriculture. Ain-Lhout et al [18] found that high intensity of herbivory pressure and human use of Argan trees reduced tree size and crow cover of A. spinosa. In another work on the same species and the same environmental context.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing generally has a negative effect on plants [13][14][15][16][17].In a previous work conducted in Admine forest, a heavily humanized area traditionally managed for livestock raising and agriculture. Ain-Lhout et al [18] found that high intensity of herbivory pressure and human use of Argan trees reduced tree size and crow cover of A. spinosa. In another work on the same species and the same environmental context.…”
Section: Introductionmentioning
confidence: 99%